2017
DOI: 10.1111/jgh.13457
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating albumin–bilirubin grade into the cancer of the liver Italian program system for hepatocellular carcinoma

Abstract: The ALBI grade performs as well as the CP grade when integrating into the CLIP system. ALBI-CLIP and CP-CLIP systems are the most accurate prognostic models among 11 existing staging systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Additionally, albumin, as part of the ALBI grading system, has been shown to be a quantitative, useful and prognostic indicator of liver dysfunction in HCC patients (21)(22)(23)(24)(25). Albumin has previously been reported to have direct HCC growth inhibitory properties in vitro (26,27), and there is also suggestive clinical evidence for an inhibitory effect on HCC in patients (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, albumin, as part of the ALBI grading system, has been shown to be a quantitative, useful and prognostic indicator of liver dysfunction in HCC patients (21)(22)(23)(24)(25). Albumin has previously been reported to have direct HCC growth inhibitory properties in vitro (26,27), and there is also suggestive clinical evidence for an inhibitory effect on HCC in patients (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because of the progress in techniques used for imaging, and therapeutic assistant modalities for the diagnosis and treatment of HCC (virtual ultrasonography [39], artificial effusion [40], contrast-enhanced ultrasonography [41,42], and Gd-EOB-DTPA-enhanced MRI [43,44]), the frequencies of resection and ablative therapies including radiofrequency ablation will increase; thus, a more suitable hepatic function assessment tool for the recent trend in Japanese HCC is needed. In addition to the usefulness of ALBI-T for Japanese patients, that of modified CLIP scoring [45], modified BCLC (Barcelona Clinic Liver Cancer) staging [46], and BCLC-B substaging using ALBI grading instead of the Child-Pugh classification/scoring system [47] has recently been reported. Thus, the simply calculated ALBI grade can play an important role in the assessment of hepatic function not only in the recent trend of Japanese HCC but also worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Omagari et al [8] reported that the liver damage classification is a more effective evaluation method for patients with early stage HCC as compared to the Child-Pugh classification. Recently, a simple evaluation method for hepatic function, termed albumin-bilirubin (ALBI) grade, which is calculated using only serum albumin and total bilirubin, has been proposed [9] , and some have reported its usefulness for HCC treatment planning [9][10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%